2016
DOI: 10.1017/s0043933916000210
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium butyrate in chicken nutrition: the dynamics of performance, gut microbiota, gut morphology, and immunity

Abstract: The effect of sodium butyrate on various bodily parameters of broilers such as performance, gut microflora, gut morphology, and immunity is reviewed in order to highlight its importance as an alternative to antibiotic growth promoters. Sodium butyrate is used as a source of butyric acid, which is known for its beneficial effects in the gut in monogastrics. Sodium butyrate is available in uncoated and entericcoated forms protected with fat or fatty acid salts. Varying results in productive performance, gut micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 47 publications
2
64
0
Order By: Relevance
“…Sodium butyrate could directly exert anti‐inflammatory effects by suppressing the transmigration (Segain et al., ) and binding activity of NFκB (Wen, Lu, & Zou, ). Dietary administered sodium butyrate (SB) can be converted to butyrate in the intestine (Ahsan et al, ). In freshwater fish, the supplementation of SB in high‐SBM diets enhanced the intestine physical barrier function referring to tight junction complexes (TJs), such as claudin, occludin and tight junction protein ZO1 (Xu et al, ), which are modulated by myosin light chain kinase (MLCK) pathways (Shen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium butyrate could directly exert anti‐inflammatory effects by suppressing the transmigration (Segain et al., ) and binding activity of NFκB (Wen, Lu, & Zou, ). Dietary administered sodium butyrate (SB) can be converted to butyrate in the intestine (Ahsan et al, ). In freshwater fish, the supplementation of SB in high‐SBM diets enhanced the intestine physical barrier function referring to tight junction complexes (TJs), such as claudin, occludin and tight junction protein ZO1 (Xu et al, ), which are modulated by myosin light chain kinase (MLCK) pathways (Shen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Gut health has extensively been studied, as the gut is considered the main site where nutrient absorption occurs (Rinttilä & Apajalahti, 2013). Impaired gut health could markedly affect the digestion, and absorption of nutrients that consequently impact the overall health, and performance of poultry (Ahsan et al, 2016). It is well known that the intestinal tract is susceptible to a majority of pathogens (Yegani & Korver, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Butyric acid is one of SCFA, which has a higher bactericidal activity (Leeson, Namkung, Antongiovanni, & Lee, 2005). Ahsan et al (2016) reported that butyric acid belongs to the class of carboxylic acids consisting of a four carbon atoms chain, thus named as butanoic acid. The hydrogen ion of hydroxyl group is weakly bonded and replaceable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that dietary supplementation of chickens with a protected source of sodium butyrate (SB) modulated the diversity, composition, and predictive function of the cecal microbiota (Bortoluzzi et al, 2017). Indeed, SB may directly modulate the intestinal microbiota, through its bactericidal effect, or indirectly by stimulating the growth of beneficial lactic acid bacteria (Ahsan et al, 2016). Additionally, essential oils (EO) obtained from plant materials are known to possess antimicrobial, antioxidant, and anti-inflammatory properties (Brenes and Roura, 2010).…”
Section: Introductionmentioning
confidence: 99%